'A way of happening, a mouth': On an Aspect of Lorca's Revision of the Old Spanish Ballads. Issue 2 (7th February 2017) - Quance, Roberta Ann
Abstract: Lorca's understanding of the nature of traditional ballads—how they were composed, performed, transmitted—shaped his own reinvention of the ballad. This article argues that Lorca wrote with Menéndez Pidal's early theories of the Romancero in mind. Therefore Lorca's ballads do not issue from a narrator, strictly speaking, but from a voice that is standing in for a juglar and which I term a textual balladeer. This figure transmits textual fragments (as analysis of the 'Burla de don Pedro a caballo' suggests) which are revived by a balladeer's imposing voice. It is all illusion but, as we see in the 'Romance sonámbulo', Lorca conceives of the ballad as the performance of a powerful voice which can cast such illusions. Therefore, the article examines sound patterning in concert with metre as a way for the textual balladeer to develop voice's agency. Lorca's divided soul, nostalgic for orality but grounded in textuality, is considered.